Smart Contract Integration In Indonesian Law: Legal Certainty And Data Protection In The Digital Age: Integrasi Kontrak Cerdas dalam Hukum Indonesia: Kepastian Hukum dan Perlindungan Data di Era Digital - Harianja, Syahban Alvian Hamonangan; Mujiburrohman; Satya, Adhika Mahindra (Perspektif Hukum, 2026)
ndonesia's digital economy ecosystem shows an increase in the adoption of blockchain and smart contracts. However, the Civil Code, the Electronic Information and Transactions Law, and the Personal Data Protection Law do not explicitly anticipate contracts executed by code, creating a legal vacuum in terms of definition, validity, technical standards, and governance of accountability. This study aims to (1) analyze the position and validity of smart contracts in Indonesia's civil law system; and (2) analyze legal liability and personal data protection in an immutable and decentralized ecosystem. The method employed is normative legal research, utilizing a legislative, conceptual, and comparative approach, with reference to European Union practices. The results show that the recognition of electronic information or documents and electronic signatures provides a legal basis; however, the absence of clear definitions and minimum clauses weakens contractual certainty, especially in cross-border transactions. Blockchain records have high evidential value as long as reliability parameters accompany them. In the realm of personal data, the tension between data subject rights and immutability can be bridged through privacy by design/default, data minimization at the on-chain layer (off-chain identity), crypto-erasure options, and zero-knowledge proofs, with role mapping of controllers and processors based on functions and data protection impact assessment obligations. Recommendations include legal recognition of smart contracts along with mandatory clauses (choice of law/forum, ADR/ODR levels, escrow/circuit breaker), pre-deployment code audits, change management, and hybrid on-chain/off-chain dispute architecture, as well as the adoption of elements of EU practice (built-in legal/jurisdictional rules and minimum technical safeguards).